How gaming, artificial intelligence and big data is changing education - Teo Peihan Janine (Journal of Games, Game Art, and Gamification, 2017)
With 263 million children and youth out of school, there is a need for a highly scalable way to provide quality education to the underprivileged. Solve Education!(SE!)â€™s solution is combining an addictive game with the â€œLearning-by-Doingâ€ Principle. Leveraging artificial intelligence and big data analysis, SE! explores the possibility of combining multi-user online strategy games with casual puzzle games to increase user retention rates, and in the process educating the users effectively over a longer period of time. Game mechanics are used to increase user retention by boosting motivation, while big data analysis allows SE! to understand the usersâ€™ in-game behavior and how they learn best. Artificial intelligence helps to deliver the right content to the user at the right time, optimizing the learning process, and enabling in-game adaption to the usersâ€™ learning needsÂ